An Almost Sure Central Limit Theorem for Weighted Sums of Mixing Sequences (Communications in Mathematical Research, 2021)
In this paper, we prove an almost sure central limit theorem for weightedsums of mixing sequences of random variables without stationary assumptions. We nolonger restrict to logarithmic averages, but allow rather arbitrary weight sequences.This extends the earlier work on mixing random variables.
Keywords: almost sure central limit theorem; weighted sum; mixing sequence; logarithmic average.